Study related to the CIPP model as a form of evaluation in training programs - Rahmadani (Balai Diklat Keagamaan Ambon, 2022)
The quality of learning in training is inseparable from the training participants and instructor who are implementing the learning program. However, an evaluation is needed as a benchmark for achieving a desired goal. One form of evaluation that is very trending in education is the CIPP (Context-input-process-product) Model developed by Stufflebeam. The results of the literature review show that in applying the evaluation of the CIPP Model at BDK Ambon, the aspect of context or goals are related to the demands of the community or the field, the aspect of input is related to ASN as a learning subject, instructor as a teaching subject, curriculum design as a learning design, media, and infrastructure as teaching aids. While the process or activities of the training participants can learn with direction, assistance, and encouragement from the instructor. And for products or results, it can be seen from the participants when they return to their work units which can be assessed directly by their respective superiors. Thus, the results of the implementation of the CIPP model can be input for superiors in making a policy.